Two new species of oribatid mites (Acari, Oribatida) with auriculate pteromorphs from Costa Rica, including a key to all species of Galumna (Galumna) of the Neotropical region - Ermilov, Sergey G. (2015)
Two species of oribatid mites with auriculate pteromorphs, Truncozetes paraecuadoriensis sp. nov. and Galumna paraoctopunctata sp. nov., are described from leaf litter of secondary forest in Costa Rica. Truncozetes paraecuadoriensis sp. nov. is most similar to T. ecuadoriensis Ermilov, Sandmann, Marian & Maraun, 2013, however, it differs from the latter by the body size, morphology of interlamellar and bothridial setae, structure of translamella and surface of epimeral region. Galumna paraoctopunctata sp. nov. is most similar to G. octopunctata (Ewing, 1909), however, it differs from the latter by the body size, structure of lamellar lines and morphology of notogastral porose areas A3. The genus Truncozetes is recorded for the first time in Costa Rica.